Mutational status of NRAS, KRAS, and PTPN11 genes is associated with genetic/cytogenetic features in children with B‐precursor acute lymphoblastic leukemia. Issue 2 (29th August 2017) - Liang, Der‐Cherng; Chen, Shih‐Hsiang; Liu, Hsi‐Che; Yang, Chao‐Ping; Yeh, Ting‐Chi; Jaing, Tang‐Her; Hung, Iou‐Jih; Hou, Jen‐Yin; Lin, Tung‐Huei; Lin, Chun‐Hui; Shih, Lee‐Yung
Abstract: Background: We aimed to investigate the frequencies and the association with genetic/cytogenetic abnormalities as well as prognostic relevance of RAS pathway mutations in Taiwanese children with B‐precursor acute lymphoblastic leukemia (ALL), the largest cohort in Asians. Procedure: Between 1995 and 2012, marrow samples at diagnosis from 535 children were studied for NRAS, KRAS, and PTPN11 mutations. The mutational status of each gene was correlated with the clinico‐hematological features, recurrent genetic abnormalities, and outcomes for those treated with TPOG‐ALL‐2002 protocol (n = 346). Results: The frequencies of NRAS, KRAS, and PTPN11 mutations were 10.8% (57/530), 10.2% (54/530), and 3.0% (16/526), respectively. NRAS mutations were associated with a higher frequency of hyperdiploidy ( P  = 0.01) and lower frequency of ETV6‐RUNX1 ( P  < 0.01), whereas KRAS mutations were associated with younger age ( P  < 0.01), a higher frequency of KMT2A rearranged ( P  < 0.01) but no significant difference if infants with ALL were excluded, and inferior event‐free survival (66.6% vs. 80.5%, P  = 0.04). None of patients with TCF3‐PBX1 had KRAS mutation ( P  = 0.02). Conclusions: Our study showed that the frequency of KRAS mutations in Taiwan was significantly higher than that reported in Caucasians. The occurrence of RAS pathway mutations was associated with recurrent genetic/cytogenetic abnormalities in pediatric B‐precursor ALL.